Selective Modification of Hierarchical Pores and Surfaces in Nanoporous Materials. Issue 4 (1st October 2020) - Tiemann, Michael; Weinberger, Christian
Abstract: Tailor‐made ordered mesoporous materials bear great potential in numerous fields of application where large interfaces are required. However, the inherent surfacechemical properties of conventional materials, such as silica, carbon or organosilica, poses some limitations with respect to their application. Surface manipulation by functionalization with chemically more reactive groups is one way to improve materials for their desired purpose. Another approach is the design of high surface‐area composite materials. The surface manipulation, either by functionalization or by introducing guest species, can be performed selectively. This means that when several distinct, i.e., hierarchical, types of surfaces or pore systems exist in a material, each of them may be chosen for manipulation. Several strategies can be identified to achieve this goal. Molecules or molecule assemblies can be utilized to temporarily protect pores or surfaces (soft protection), while manipulation occurs at the accessible sites. This approach is a recurring motive in this review and can also be applied to rigid template matrices (hard protection). Furthermore, the size of functionalization agents (size protection) and their reactivity/diffusion (kinetic protection) into the pores can also be utilized to achieve selectivity. In addition, challenges in the synthesis and characterization of selectively manipulated ordered mesoporous materials are discussed. Abstract : Ordered mesoporous materials exhibit several distinct types of surfaces or pore systems (e.g., internal and external surface). This review summarizes the main strategies to achieve a spatial distribution of functional groups or the deposition of a guest species. Furthermore, characterization techniques and applications of such tailor‐made materials are discussed, as well as an outlook about potential future trends.